Endolumenal Rectal Resection and Transanal Natural Orifice Specimen Extraction (NOSE) Without Rectal Stump Opening: A Novel, Clean Surgical Technique in a Porcine Model. (October 2013) - Kvasha, Anton; Kvasha, Vladimir; Hadary, Amram; Willenz, Udi; Szvalb, Sergio; Waksman, Igor
Minimally invasive surgery has been continuously evolving over the past 20 years. The use of natural orifice specimen extraction (NOSE) is one of the most recent contributions to minimally invasive methods. The anus has been widely used in NOSE procedures. However, an open rectal stump carries the highest risk of contamination compared with other translumenal approaches to the peritoneal cavity. In this study, the feasibility of a novel NOSE method was tested in a porcine model. This technique combined abdominal and transanal approaches. The abdominal approach was used in rectal mobilization; this was followed by a transanal recto-rectal intussusception and pull-through (IPT). IPT was established in a stepwise fashion. First, the proximal margin of resection was attached to the shaft of the anvil of an end-to-end circular stapler with a ligature around the rectum. Second, this complex was pulled transanally to produce IPT. Once IPT was established, a second ligature was placed around the rectum, approximating the proximal and distal resection margins. The specimen was resected and extracted by making a full-thickness incision through 2 bowel walls distal to the previously placed ligatures. Anastomosis was achieved by applying the stapler. The technique was found to be feasible. A substantial length of bowel was resected in all experiments. Peritoneal samples, collected after transanal specimen extraction, did not demonstrate bacterial growth. Although more investigation is warranted, this procedure has the potential to limit surgical site infections by using aseptic bowel manipulation during colorectal resection and transanal specimen extraction.